From Interaction to Transaction: Analyzing the Influence of Social Presence on Impulsive Purchasing in Live Streaming Commerce - Andika; Tiara Nur Anisah; Mohamad Najmudin; Anita Ekawati Sardi (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study investigates how social presence elements, such as streamers, other viewers, and products, directly and indirectly influence consumers' impulse purchase behaviour in live-streaming commerce. Design/Methods/Approach: An empirical evaluation was conducted on the suggested model, utilizing survey responses from 205 live-streaming commerce users. Furthermore, the interconnections among the elements within the research framework were examined through SEM PLS version 3. Findings: The results show that social presence directly and significantly affects impulse purchase behaviour. This study also strongly links social presence with perceived usefulness and positive affect. In addition, the results show that perceived usefulness and positive affect significantly influence impulse purchase behaviour. Interestingly, perceived usefulness and positive affect serve as potential intermediaries linking the impact of social presence with impulse purchase behaviour. Originality/Value: This research explores the influence of social presence and several consumer psychological factors, such as perceived usefulness and positive affect, on impulse purchase behaviour in live-streaming commerce. While this area has rarely been a significant focus in previous literature, the speciality of this research is integrating the product dimension into the social presence framework. This initiative has yet to be found in the literature so far. With this approach, the research seeks to provide an in-depth understanding of how social presence elements such as streamers, other viewers, and products collaborate and directly and indirectly impact impulse buying behaviour. Practical/Policy implication: The results of this study offer a significant perspective for businesses in the e-commerce sector and individuals producing content for live-streaming commerce. This information can be used to create better approaches to encourage impulse buying behaviour and increase customer interaction. The interaction between social presence, perceived usefulness, and positive affect can be the basis for designing more efficient strategies.